Green natural rubber-g-modified starch for controlling urea release - Sa Ad Riyajan (2018)
The hydrophilicity of natural rubber (NR) was improved by grafting with modified cassava starch (ST) (NR-g-ST) by using potassium persulfate (K 2 S 2 O 8 ) as a catalyst. The modified ST was added to NR latex in the presence of Terric16A16 as a non-ionic surfactant at 60°C for 3 h and cast film on a glass plate to obtain NR-g-ST. The chemical structure of NR-g-ST was confirmed by FTIR. The swelling ratio of NR-g-ST was investigated in water and results showed that the swelling ratio of the modified NR decreased as function of ST. In addition, the tensile strength of the modified NR in the presence of modified ST at 50 phr was the highest value. Also, the thermal stability modified NR-g-ST was higher than of NR/ST blend confirmed by TGA. Finally, the NR-g-ST was used a polymer membrane for controlling urea fertilizer and it easily degraded in soil. This product with good controlled-release and water-retention could be especially useful in agricultural and horticultural applications. © 2012 Elsevier Ltd. All rights reserved.